2019
DOI: 10.1371/journal.pone.0222263
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory assessment of alternative stream velocity measurement methods

Abstract: Understanding streamflow in montane watersheds on regional scales is often incomplete due to a lack of data for small-order streams that link precipitation and snowmelt processes to main stem discharge. This data deficiency is attributed to the prohibitive cost of conventional streamflow measurement methods and the remote location of many small streams. Expedient and low-cost streamflow measurement methods used by resource professionals or citizen scientists can provide scientifically useful solutions to this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Mean vertical velocities ( V ) were calculated from surface velocity ( V s ) measurements for the SF and VR methods using Equations ():V=Vnormals×α,α=0.00628×d+0.456for gravel and cobbleconditions,andα=0.92for smooth conditions,where α is the surface velocity ratio and d is the measured depth in cm. The relationships in Equations () were derived in a controlled laboratory flume setting (Hundt and Blasch 2019) and are presented in tabular form in Table S4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean vertical velocities ( V ) were calculated from surface velocity ( V s ) measurements for the SF and VR methods using Equations ():V=Vnormals×α,α=0.00628×d+0.456for gravel and cobbleconditions,andα=0.92for smooth conditions,where α is the surface velocity ratio and d is the measured depth in cm. The relationships in Equations () were derived in a controlled laboratory flume setting (Hundt and Blasch 2019) and are presented in tabular form in Table S4.…”
Section: Methodsmentioning
confidence: 99%
“…The basic premise is that the difference in water levels (head) between the upstream and downstream sides of a stationary object placed in an open channel is proportional to the water velocity following the Bernoulli Principle (Figure 3). The head is typically measured as the difference between the upstream and downstream sides of a transparent object using a graduated ruler, and related to velocity through an empirical equation (Hundt and Blasch 2019). Fonstad et al (2005) reported that precision of 5% in velocity can be achieved with this approach.…”
Section: Jawramentioning
confidence: 99%
“…The water depth of both lotic and lentic water bodies was measured by inserting a meter ruler in the water until it came in contact with the bed. The velocity of the water was determined using floats (Hundt and Blasch, 2019) whereby the float was released upstream to cover a distance of 10 m. The time taken by the float to cover the…”
Section: Recording Of Altitude Slope Aspect Water Depth and Velocitymentioning
confidence: 99%
“…145 | P a g e 10 m distance was recorded. With the recorded time and distance, the velocity of the water was calculated as per the formula adopted by Hundt and Blasch (2019).…”
Section: International Journal Of Environment Issn 2091-2854mentioning
confidence: 99%
“…For the rest of the reaches, due to safety and accessibility considerations, only the second method was used, and flow velocities were corrected by a factor of 0.65 to obtain a more representative value of the water column profile. The corrector factor is based on research using both a current meter and the float method in other rivers in the Coquimbo region (Oyarzún et al, 2016) and elsewhere (Hundt & Blasch, 2019). Stream widths were manually measured at regular intervals (i.e., every 10-20 m) with a measuring tape, and the water column depths were measured with a graded pole, when possible.…”
Section: Field Workmentioning
confidence: 99%